2017
DOI: 10.1080/09513590.2017.1395839
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of a meningioma in a transwoman after nine years of cyproterone acetate and estradiol intake: case report and literature review

Abstract: The administration of cyproterone acetate (CPA) and estradiol is a common regimen used by male-to-female transsexuals (transwoman) to adjust their body to their gender identity. Major adverse events are uncommon in these subjects in spite of long-term, high dose cross-sex steroid treatments. We describe the occurrence of a meningioma in a transwoman treated with estrogens and CPA over a period of nine years. The meningioma was revealed during a magnetic resonance imaging (MRI) scan performed as follow-up of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 27 publications
0
19
0
6
Order By: Relevance
“…Altri suggerimenti di una possibile associazione tra progesterone/progestinici e meningiomi sono emersi da casi di pazienti in terapia cronica con progesterone per diverse ragioni mediche quali linfangioleiomiomatosi, ipertrofia prostatica benigna o irsutismo. Nel 2006, Pozzati e collaboratori hanno documentato un caso di rapida crescita di meningiomi multipli intracranici in una donna in postmenopausa trattata con medrossiprogesterone acetato per linfangioleiomiomatosi; successivamente alla sua sospensione, le lesioni sono regredite spontaneamente [10]. Nel 2010, Goncalves e colleghi hanno registrato la rapida regressione di un meningioma dopo interruzione del trattamento con ciproterone acetato (50 mg) assunto per 10 anni da una donna biologica di 46 anni per alopecia androgenetica.…”
Section: Meccanismi Determinantiunclassified
See 2 more Smart Citations
“…Altri suggerimenti di una possibile associazione tra progesterone/progestinici e meningiomi sono emersi da casi di pazienti in terapia cronica con progesterone per diverse ragioni mediche quali linfangioleiomiomatosi, ipertrofia prostatica benigna o irsutismo. Nel 2006, Pozzati e collaboratori hanno documentato un caso di rapida crescita di meningiomi multipli intracranici in una donna in postmenopausa trattata con medrossiprogesterone acetato per linfangioleiomiomatosi; successivamente alla sua sospensione, le lesioni sono regredite spontaneamente [10]. Nel 2010, Goncalves e colleghi hanno registrato la rapida regressione di un meningioma dopo interruzione del trattamento con ciproterone acetato (50 mg) assunto per 10 anni da una donna biologica di 46 anni per alopecia androgenetica.…”
Section: Meccanismi Determinantiunclassified
“…L'ipotesi di una relazione tra tumori cerebrali benigni e CPA ad alte dosi è supportata in letteratura da alcune (n = 9) segnalazioni di singoli casi (Tabella 1) anche in individui transgender in corso di terapia gender affirming, come meningiomi e prolattinomi [3,10] in donne transgender e un caso di somatotropinoma in un uomo transgender [13].…”
Section: Meccanismi Determinantiunclassified
See 1 more Smart Citation
“…In transwomen, prostate cancer risk is expected to be extremely low due to gland atrophy after pubertal medical castration. Long-term use of high-dose anti-androgens is of concern (103). A retrospective study observed a higher incidence of meningioma in a cisgender population using cyproterone acetate, especially when higher doses were used; however, further research is warranted (104).…”
Section: Follow-up and Long-term Carementioning
confidence: 99%
“…[ 18 ] A few previous case reports have described rapid development and growth of meningiomas in transsexual individuals taking sex-hormone replacement therapy (HRT). [ 8 9 15 17 ] On the other side of the spectrum, regression meningiomas after discontinuation of HRT have also been described. [ 5 10 17 ]…”
Section: Introductionmentioning
confidence: 99%